(untitled) (Revista Direito em Debate, 2019)
The research of this bibliographic research seeks, if the Legal Realism has elements that connect it to the Legal Positivism. We began the main aspects of Legal Realism along with its theorists, demonstrating its strong antiformalist characteristic. In a second moment, we highlight some points of Legal Positivism based on some of its theorists. The final show me the points of connection between the two currents of thought, thus clarifying their approximation.